Bourgeois Visions of Urban Space in Nineteenth-Century Quebec - Young, Brian J. (Frontières flottantes: Lieu et espace dans les cultures francophones du Canada / Shifting Boundaries: Place and Space in the Francophone Cultures of Canada, 2001)
Keywords: Bourgeoisie

Elsie Reford, une bourgeoise montréalaise et métissienne. Un exemple de spatialisation des sphères privée et publique - Hébert, Karine (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Bourgeoisie

« What a Misfortune that Poor Child Should Have Married Such a Being as Joe »: Les fils prodigues de la bourgeoisie montréalaise, 1850-1900 - Nootens, Thierry (Canadian Historical Review, 2005)
Number: 2
Keywords: Bourgeoisie

George-Étienne Cartier, bourgeois montréalais - Young, Brian (Boréal, 2004)
Translators: _:n32786
Keywords: Bourgeoisie; Cartier; George-Étienne

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

Elsie Reford, au-delà des jardins - Hébert, Karine (Elsie: une œuvre hommage de Dominique Blain / Elsie: a Tribute by Dominique Blain, 2007)
Keywords: Bourgeoisie

Mondanité et vie culturelle. Prescriptions et espace public - Cambron, Micheline (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Bourgeoisie

Le nectar et l’ambroisie. La consommation des boissons alcooliques chez l’élite de la Nouvelle-France au XVIIIe siècle - Ferland, Catherine (Revue d'histoire de l'Amérique française, 2005)
Number: 4
Keywords: Alcool; Bourgeoisie

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
issued: 2009-23-00
Keywords: Bourgeoisie; Femmes

Les règles du jeu de la séduction dans les manuels de savoir-vivre québécois (1863-1917): investir le monde du sentiment et de l’intimité masculine - Roy, Sonya (Université de Montréal, 2006)
Keywords: Bourgeoisie; Mariage

L’idéologie de la pauvreté chez l’élite canadienne-française du XIXe siècle (1850-1900) - Pomerleau, Colette (Université du Québec à Montréal, 2006)
Keywords: Bourgeoisie; Idéologies; Pauvreté

Class, Gender, and the Social Standard: The Montreal Junior League, 1912–1939 - Chenier, Elise (Canadian Historical Review, 2009)
Number: 4
Keywords: Anglophones; Bourgeoisie; Femmes

Un artiste au quotidien au tournant du XXe siècle: le cas de Ludger Larose, 1868-1915 - Longstaff, Alison (Université du Québec à Trois-Rivières, 2008)
Keywords: Bourgeoisie; Francophones; Francs-Maçons; Peinture

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La vie de château - Dugas, Marcel (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Château Dufresne; Golden Square Mile; Logement; Mount Stephen Club

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac